Quality Assurance in Testing of Highway Materials in Pakistan - Qureshi, Abdul Sami; Soomro, Shakeel Ahmed; Memon, Nafees Ahmed (International Journal of Sustainable Construction Engineering and Technology, 2021)
In Pakistan three modes of transportation are usually used. It is believed that road sector is the major source of transport, which carries about 92 percent of travelers and 96 percent of cargo traffic. There are various factors which may cause the deterioration of pavement such as inadequate drainage, frost action, unsatisfactory compaction and overloading etc. One of the important factors seriously affecting the pavement performance is quality of material. Although some research work has been carried out related to use of required quality materials in highway construction; however, limited research has been done related to quality assurance in testing of highway materials in commercial laboratories. As the approval of material usage mainly depends upon testing reports provided by laboratories, therefore poor quality assurance system of testing laboratories may have adverse effect on material approvals. Rapid growth of population in Pakistan demands expansions in highway constructions; therefore, assessment and improvement of quality assurance will ensure proper usage of required quality materials. In the above mentioned context assessment of few commercial laboratories involved in highway material testing was done in comparison to public sector laboratory. The results indicate that there are significant variations in test results carried out at different commercial laboratories. Based on the assessment the study highlights the improvement areas to raise the standard of quality assurance in highway material testing in Pakistan.